IMPLEMENTASI MAQĀṢID AL-SHARĪ'AH DALAM HUKUM EKONOMI ISLAM - Syufa'at Syufa'at (Faculty of Sharia and Law, Universitas Islam Negeri (UIN) Walisongo Semarang, 2013)
The objective revelation of Islamic law is to create public interest (maṣlaḥat), both individually and collectively. The public interest that mentioned in Islamic law is the true goodness, not the pseudo benefit which influenced human desires. The Public interest here includes physical and spiritual. The public interest that intended by Islamic law is the goodness in this life and in the hereafter, not solely in the world live. maslahah in the Shariah perspective is based on five principles called al-mabādi'al-khamsah or al-uṣūl alkhamsah namely: keeping religion (hifẓ al-dīn), keeping the soul (hifẓ al-nafs), keeping mind (hifẓ al-‘aql), keeping property (hifẓ al-māl), and keeping descent (hifẓ al-nasl). Maqāṣid al-sharī’ah implementation of some economic problems is to answer the reality of modern society to face the challenges of basic needs such as clothing, food, shelter, health, education, employment, sanitation, energy, transport and information. Crucial needs of modern man is the spiritual and ethical, because modern society only measure the welfare just from the outer side only, that is to meet the needs according to the principle of utility and pragmatism